2016
DOI: 10.1111/pde.12986
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Analysis of Onychomycosis in the San Diego Pediatric Population

Abstract: Our study provides important regional information regarding epidemiologic data in pediatric onychomycosis, highlighting the diagnostic methods most commonly used and the pathogens most frequently encountered in our practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…The high prevalence of fungal infections in North America is largely due to the immigration of dermatophytes from other areas of the world such as West Africa and Southeast Asia. The global prevalence of onychomycosis is estimated to be around 5.5%, attributing to 50.0% of all nail disease cases . The risk of onychomycosis increases with age due to poor peripheral circulation, diabetes, repeated nail trauma, longer exposure to pathogenic fungi, suboptimal immune function, inactivity, and/or the inability to maintain good foot care .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of fungal infections in North America is largely due to the immigration of dermatophytes from other areas of the world such as West Africa and Southeast Asia. The global prevalence of onychomycosis is estimated to be around 5.5%, attributing to 50.0% of all nail disease cases . The risk of onychomycosis increases with age due to poor peripheral circulation, diabetes, repeated nail trauma, longer exposure to pathogenic fungi, suboptimal immune function, inactivity, and/or the inability to maintain good foot care .…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of childhood onychomycosis ranges worldwide from 0.35% to 5.5%, causing 15.5% of all child nail dystrophies . Recent studies have suggested that the occurrence of onychomycosis in children has increased .…”
Section: Special Populationsmentioning
confidence: 99%
“…Onychomycosis is a fungal infection of the nail unit commonly caused by dermatophytes . Recent studies suggest that onychomycosis has a worldwide prevalence of 5.5%, with a 8.9% prevalence in hospital‐based studies and 4.3% in population‐based studies . Recurrence and relapse are frequently (10–53%) associated with this infection despite the use of treatment, with relapse likely to occur within 2.5 years after successful treatment .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of pediatric onychomycosis appears to be increasing. Gupta et al reported a prevalence of 0.44% in 1997 in North American children, and Totri et al documented a 1% incidence of onychomycosis in a 2017 retrospective study. An increase in pediatric onychomycosis has also been observed in India, Spain, Iceland, Poland, Israel, and Turkey …”
Section: Discussionmentioning
confidence: 99%
“…Onychomycosis in children (0.14%) is less frequent than in adults (3.2%) . The prevalence of childhood onychomycosis ranges worldwide from 0.35% to 5.5% and is reported to cause 15.5% of all nail dystrophies in children . A number of studies have demonstrated an increase in the occurrence of onychomycosis in children .…”
Section: Introductionmentioning
confidence: 99%